Application of bidimensional shear wave liver elastography in the pediatric population - Paula Maria Dyba; Jakub Potoczny; Tomasz Waszak; Karolina Siwierska; Katarzyna Jończyk-Potoczna (Termedia Publishing House, 2023)
Chronic liver diseases are a notable worldwide problem among adults and children. Pediatric chronic liver diseases have a wide range of etiologies, including congenital, metabolic, toxic, and infectious backgrounds, as well as fatty liver disease. Patients with more advanced stages of fibrosis are more likely to develop cirrhosis with all of its complications. Severity of liver fibrosis and its progression are among the most important factors for the prognosis and treatment policy. Liver biopsy is still considered as a reference standard to quantify liver fibrosis, but it is not a good tool for regular monitoring of disease progression. For these reasons, nowadays huge development of noninvasive methods for the assessment of liver fibrosis can be observed. Ultrasound elastography methods are widely accessible and easily performed in children. Bi-dimensional shear-wave elastography is one of the newest elastography techniques.